2012
DOI: 10.1177/1076029612437576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uremia and Hemodialysis on Platelet Apoptosis

Abstract: The blood platelet proteome of hemodialyzed patients with uremia exhibits significant difference in comparison with the blood platelet proteome of healthy individuals. This alteration is manifested by the presence of high concentrations of low-molecular peptides within the whole range of isoelectric points. Increased platelet apoptosis has been put forward as a possible cause of this phenomenon. The aim of the present research was to assess whether blood platelet populations from hemodialyzed patients with ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…PLT activation might happen during the dialysis session [44]; however, dialysis often reduces the PLT activation markers [44,45]. This was also observed in our patients through decrease in the CD62P + PLTs, as a probable result of HD-induced cell clearance [46] or increased microvesiculation [47]. The persistently increased PFA values of ESRD patients that were not affected by the dialysis session in contrast to the P-selectin expression levels that were decreased, imply that platelet dysfunction (reflected in the PFA values) is independent of P-selectin expression in ESRD patients, as previously described in children with iron deficiency anemia [48].…”
Section: Discussionsupporting
confidence: 74%
“…PLT activation might happen during the dialysis session [44]; however, dialysis often reduces the PLT activation markers [44,45]. This was also observed in our patients through decrease in the CD62P + PLTs, as a probable result of HD-induced cell clearance [46] or increased microvesiculation [47]. The persistently increased PFA values of ESRD patients that were not affected by the dialysis session in contrast to the P-selectin expression levels that were decreased, imply that platelet dysfunction (reflected in the PFA values) is independent of P-selectin expression in ESRD patients, as previously described in children with iron deficiency anemia [48].…”
Section: Discussionsupporting
confidence: 74%
“…Instead a large number of studies using experimental models and human subjects have shown that uremia is associated with apoptosis in a wide range of cells and tissues such as skeletal muscle [19,20] , myocardium [21] , platelets [22,23] , monocytes [24] , neutro phils [25] , lymphocytes [26] , leukocytes [27] and vascular endothelial cells [28] . The kidney has also been shown as a target for apoptosis in uremia with both podocytes [29] and proximal tubular cells identified as having increased apoptotic cell death [30] .…”
Section: Uremia Induced Apoptosismentioning
confidence: 99%
“…In patients with CKD, increased platelet apoptosis results in their shorter life-span. 12 As a result, reduced platelet count occurs in patients with CKD, which, in turn, increases blood thrombopoietin levels. A slightly reduced platelet count (229,000 per µ l in CKD versus 262,000 per µ l in controls) was shown to correlate with increased bleeding time in patients with CKD receiving hemodialysis 4 and in those not on dialysis.…”
Section: Platelet Count and Risk Of Bleeding In Ckdmentioning
confidence: 99%